Análisis del sistema de facturación electrónica y su aplicación en las empresas del Parque Industrial de la ciudad de Loja. - Quille Montoya, Mary Susana (2024)
Electronic invoicing is a modality that was implemented as of November 29, 2022, mandatory for all taxpayers except those who belong to the Popular RIMPE Regime; However, its problem lies in the lack of knowledge of the new provisions, as well as in the technological field for users to adapt, which is why the purpose of this research was to identify the advantages and disadvantages that this system has and how it affects the tributaries that are located in the Loja Industrial Park that should have been governed by current regulations; The applied methodology has a Quantitative and Qualitative approach, the first stage of the research consisted of the preparation of a survey, which was carried out to obtain objective responses related to the analysis of electronic invoicing, the 17 companies that operate normally in the Industrial Park, were answered by the owners, accountants and administrators, the questions asked focused on various relevant aspects, such as the benefits and disadvantages, the level of knowledge and training received, the choice between private software or free, among other topics of interest. In the results obtained, it was evident that the implementation of this system has brought with it several benefits such as security, speed in issuing a receipt, reduction of costs and physical spaces for the storage of documents, avoidance of forgery and fraud, help to paper reduction, among others. The adoption of electronic invoicing facilitates access to information, and also considerably speeds up taxpayers' commercial transactions. This greater agility has a positive impact on commercial and financial operations, promoting an environment of greater efficiency and productivity.